Analysis of the Drive Shaft Fracture of the Conveyor Belt for Transport of Coal - Mile Savković; Milan Dedić; Goran Pavlović; Miodrag Arsić; Zoran Stamenić (Tehnički Vjesnik, 2019)
The conveyor belt for slag and coal transport in the open mine pit "Kolubara" – Serbia is driven by means of two drive drums, attached on separate shafts. Each shaft is driven by two electric motors on both sides. During exploitation, the conveyor belt drive shafts are subjected to torques and transverse forces due to belt tension. The gearboxes and the bearing units on both sides of the drive drum support each shaft. A fracture of one of the drive shafts of the conveyor belt occurred at its connection point with the gearbox. The first part of the paper defines the loads relevant for shaft calculation, based on measurements in different phases of operation and the manufacturer’s data. It is followed by the FEM analysis and fatigue analysis, for the most unfavourable load case. It has been established that the critical stress value has occurred near the connection point between the shaft and the gearbox, in the fracture zone. The second part of the paper presents chemical composition and mechanical properties of material, as well as metallographic examination of fracture surface. The experimental test procedure shows that the fracture has occurred not because of an error in the material but as a consequence of the inadequate heat treatment. Superposition of two negative influences: material fatigue and inadequate heat treatment, expressed in the cross section at the point of fracture is the main case of the conveyor belt shaft fracture.